2020
DOI: 10.1002/uog.20413
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different fetal growth charts in prediction of large‐for‐gestational age and associated neonatal morbidity in multiethnic obese population

Abstract: Objectives To examine the performance of different fetal growth charts in the prediction of large‐for‐gestational age (LGA) and associated neonatal morbidity at term in a multiethnic, obese population. Methods This was a retrospective cohort study of 253 non‐anomalous, singleton, term pregnancies that underwent serial third‐trimester ultrasound scans due to maternal body mass index ≥ 35 kg/m2. We compared the performance of the Hadlock, Gestation Related Optimal Weight (GROW), INTERGROWTH‐21st (IG‐21), World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…Furthermore, we acknowledge that applying BW of the study population to the EFW standards introduced some bias into our results, particularly in preterm cases 6,7 . However, the diagnostic accuracy and sensitivity measures for perinatal mortality and neonatal morbidity when applying BW to the Hadlock-EFW and IG-21 st -EFW were similar to those of recent studies that applied ultrasound fetal measurements to the same EFW standards 37,38 . Finally, the use of the summary index of AUC from the ROC curve is a measure for predictive ability and might not provide clinically relevant meaning 35 .…”
Section: Strengths and Limitationssupporting
confidence: 75%
“…Furthermore, we acknowledge that applying BW of the study population to the EFW standards introduced some bias into our results, particularly in preterm cases 6,7 . However, the diagnostic accuracy and sensitivity measures for perinatal mortality and neonatal morbidity when applying BW to the Hadlock-EFW and IG-21 st -EFW were similar to those of recent studies that applied ultrasound fetal measurements to the same EFW standards 37,38 . Finally, the use of the summary index of AUC from the ROC curve is a measure for predictive ability and might not provide clinically relevant meaning 35 .…”
Section: Strengths and Limitationssupporting
confidence: 75%
“…They found that all charts perform well in both diagnosing LGA and predicting adverse outcomes, but the Hadlock and GROW have less false positives and may reduce the number of interventions. We must highlight that the study by Verger et al 16 was, however, specific to obese women. When we compare these 3 charts we found that they are all statistical predictors for LGA, but none of them accurately predicted adverse neonatal outcomes.…”
Section: Discussionmentioning
confidence: 81%
“…The optimal fetal growth chart to identify LGA is yet to be determined. Verger et al 16 compared the Hadlock, GROW, INTERGROWTH‐21 st , World Health Organization, and FMF fetal growth reference charts with the aim to identify the best growth chart to detect LGA in obese women at term. They found that all charts perform well in both diagnosing LGA and predicting adverse outcomes, but the Hadlock and GROW have less false positives and may reduce the number of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Primary outcomes: Actual birthweight percentile at <10th (small for gestational age [SGA]), as previously defined (Sovio et al 7 ), and actual birthweight percentile at >90th (large for gestational age [LGA]), as previously defined (Verger et al 9 ), using the United Kingdom 1990 reference (Freeman et al 10 ).…”
Section: Resultsmentioning
confidence: 99%